1996
DOI: 10.1590/s0004-282x1996000100009
|View full text |Cite
|
Sign up to set email alerts
|

Eletrencefalograma digital com mapeamento em demência de Alzheimer e doença de Parkinson: estudo prospectivo controlado

Abstract: RESUMO -Com o intuito de estudar a atividade eletrencefalográfica em vigilia da demência senil de tipo Alzheimer (DA) e da doença de Parkinson (DP) foi iniciado estudo prospectivo e controlado. Foram comparados 6 pacientes com DA e 11 pacientes com DP, com um grupo controle composto por 12 pacientes com depressão maior crônica leve a moderada (DSM-III-R, 1987). Nos três grupos, através de análise espectral, foi obtida a mediana da frequência da energia da atividade dominante posterior. O grupo controle apresen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
5
0
3
Order By: Relevance
“…Background frequency displacement to delta and theta frequencies and the dropout of central alpha rhythm are common EEG findings in AD [6]. Accordingly, Sandmann et al [7] observed a direct correlation between the degree of cognitive impairment and the power of low-frequency electrical activity in the EEG.…”
Section: Introductionmentioning
confidence: 99%
“…Background frequency displacement to delta and theta frequencies and the dropout of central alpha rhythm are common EEG findings in AD [6]. Accordingly, Sandmann et al [7] observed a direct correlation between the degree of cognitive impairment and the power of low-frequency electrical activity in the EEG.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, 72 an inverse correlation between the degree of cognitive impairment and the power of low frequency electrical activity in the EEG was observed. Since the first studies of qEEG, 73 , 74 the spectral analysis and other statistics have been applied to EEG. A decrease in alpha and beta activities have been observed in various studies published over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Muitos autores mostraram que há correlação significativa entre o grau de comprometimento cognitivo e o alentecimento da atividade elétrica cerebral de base (Dierks et al, 1991;Leuchter et al, 1993;Miyauchi et al, 1994;Sandmann et al, 1996;Rodriguez et al, 1999;Hatz et al, 2013). Segundo Edman et al (1995), as primeiras disfunções cerebrais seriam detectadas nos lobos parietais.…”
Section: Eletroencefalogramaunclassified